2017
DOI: 10.3389/fmicb.2017.01944
|View full text |Cite
|
Sign up to set email alerts
|

Autoinducer-2 Facilitates Pseudomonas aeruginosa PAO1 Pathogenicity in Vitro and in Vivo

Abstract: Bacterial communication systems, such as quorum sensing (QS), have provided new insights of alternative approaches in antimicrobial treatment. We recently reported that one QS signal, named as autoinducer-2 (AI-2), can affect the behaviors of Pseudomonas aeruginosa PAO1 in a dose-dependent manner. In this study, we aimed to investigate the effects of AI-2 on P. aeruginosa PAO1 biofilm formation and virulence factors production in vitro, and in vivo using a pulmonary infection mouse model. Exogenous AI-2 result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 43 publications
0
26
0
Order By: Relevance
“…For example, AI-2 produced by Enterococcus faecalis leads to enhanced aggregation and biofilm formation by E. coli as well as coaggregation of these two species 14 , 41 . Patients of cystic fibrosis and other disease conditions are often co-infected by P. aeruginosa and AI-2-producing bacterial species such as Staphylococcus aureus, Klebsiella pneumoniae and Streptococcus mitis 17 , 18 , 40 . The observation that PctA and TlpQ facilitate the response of P. aeruginosa toward AI-2 may explain why AI-2 in cystic fibrosis lungs enhances the virulence of P. aeruginosa 16 18 , 40 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, AI-2 produced by Enterococcus faecalis leads to enhanced aggregation and biofilm formation by E. coli as well as coaggregation of these two species 14 , 41 . Patients of cystic fibrosis and other disease conditions are often co-infected by P. aeruginosa and AI-2-producing bacterial species such as Staphylococcus aureus, Klebsiella pneumoniae and Streptococcus mitis 17 , 18 , 40 . The observation that PctA and TlpQ facilitate the response of P. aeruginosa toward AI-2 may explain why AI-2 in cystic fibrosis lungs enhances the virulence of P. aeruginosa 16 18 , 40 .…”
Section: Discussionmentioning
confidence: 99%
“…There might be something, which was commonly secreted by Gramnegative bacteria, especially in E. coli, and it could affect the development of CRPA. In recent years, a new regulating mechanism defined as quorum sensing was found to play an important role in biofilm formation [29] The signaling molecules of quorum sensing mainly contain two parts, oligopeptides are commonly secreted by Gram-positive bacteria, while N-acyl-L-homoserine lactones (AHLs) are commonly secreted by Gramnegative bacteria [30]. AHLs are one of the most wellcharacterized signaling molecules, and it was called the talking language in Gram-negative bacteria [31].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown an interplay between quorum sensing and biofilm formation [42,43]. For instance, AI-2 production or uptake has been shown to influence E. coli biofilm formation via an effect on flagellar motion and motility [44], as well as biofilm formation by Pseudomonas aeruginosa [45] and S. enterica serovar Typhimurium [46]. K. pneumoniae forms biofilms on various surfaces, where cell attachment is dependent on the production of exopolysaccharides and adhesive proteins such as type 3 fimbriae [47][48][49][50].…”
Section: Assessment Of Biofilm Formation By a K Pneumoniae δLuxs Mutantmentioning
confidence: 99%